Marriage Decision Making For Unmarried Career Women - Murti, Vanessa Jasmine; Soleh Amini (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The phenomenon of marriage postponement among career women is increasing in Indonesia, with 17.18% of women choosing to marry at age 25 and above (BPS, 2024). This study aims to describe the marriage decision-making process among career women based on Theory of Planned Behavior (TPB). The research employs a qualitative phenomenological approach with four career women informants aged 21-28 years who have worked for at least one year. Data were collected through semi-structured interviews and analyzed using Miles and Huberman's (1994) model. The findings reveal: (1) in terms of attitude toward behavior, career women position their careers as a foundation for independence before marriage with varying readiness based on career stages; (2) in terms of subjective norm, all informants face social expectations but are able to negotiate them through various strategies; (3) in terms of perceived behavioral control, mental and financial readiness are key factors with barriers including demanding work schedules. The study concludes that a paradigm shift has occurred where marriage is no longer viewed as the only path to happiness, but rather a life choice requiring careful consideration. Modern career women possess strong agency in determining marriage timing according to personal and professional conditions.